BALLISTIC STRENGTH OF WOVEN FABRICS FOR PERSONAL PROTECTION - Dimeski, D.; Spaseska, D.; Srebrenkoska, V. (Journal of Engineering & Processing Management, 2009)
The purpose of the research was to make evaluation of the ballistic strength of four different fiber/resin composites intended to be used in manufacturing of ballistic items for personal protection. Research has been performed on glass, ballistic nylon, aramid and HPPE (High Performance Polyethylene) plain woven fabrics based composites. As a matrix system, in all cases, polyvinylbutyral modified phenolic resin was used. For the investigation, areal weight range 2-9 kg/m2 , applicable range for this items, and resin content range was 20 -50. %. Ballistic test of the composites has shown that the best results exhibit HPPE based composites: aramid based composites have been the second best, followed by the polyamide based composites. The worst results have been shown by the glass based composites. All the composites with lower resin content (~20 %) have performed much better than their counterparts with higher resin content (~50 %). The plot of the ballistic strength, V50 , versus areal weight has shown a linear increase of V50 with the increase of areal weight within the investigated range. The ballistic strength of the woven fabric composites is highly dependent on the fiber/resin ratio and increases with the increase of fiber content.